Laser Doppler Flowmetry Imaging To Determine Average Velocity Of Microcirculation On Foot Using Cmos Camera (Asian Journal of Current Engineering and Maths, 2014)
A method and apparatus for non-invasive measurement of blood glucose concentration based on transilluminated laser beam via the dorsal pedis has been reported in this paper. This method depends on atomic gas (diode laser operating at 785 nm wavelength. This method would enable the monitoring blood flow of the different subjects continuously, safely and noninvasively.